Information gap amongst animal bite victims and their care givers: a study conducted at anti rabies centers of a city in North India - Singh, Amudeep; Singh, Amarjeet (International Journal Of Community Medicine And Public Health, 2018)
Background: Animal bites are a neglected public health problem. The irony is that majority of mortalities are due to unawareness of wound management procedures and prevailing various myths and misconceptions. There is dearth of evidence pertaining to it thus we aim to ascertain the information gap amongst victims regarding various aspects of managing animal bites. Methods: A cross sectional study was undertaken at ARCs of Chandigarh. 100 purposively selected animal bite victims were interviewed from January 2015 to April 2015. Information Gap was ascertained by using pre tested semi structured questionnaire. Data was analyzed using EpiInfo and MS Excel. Results: An overall high information gap of 63.5% was seen amongst the knowledge of respondents’ i.e. materials to be used, time and duration for wound washing; place of reporting; knowledge pertaining to disease caused by animal bites and it’s prevention strategies; vaccination related information; location and timing of ARCs. Conclusions: A definitive information gap needs to be addressed through to implementation of public health promotion based programmes.